Engendering economics : conversations with women economists in the United States - Olson, Paulette I., 1949- (Routledge, 2003)
Between 1950 and 1975, the percentage of women receiving economic doctorates in the US sunk to an all time low. This book consists of a series of interviews with the pioneering few who did attain this status during that period.